2010
DOI: 10.1002/jbm.a.32661
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a nanothickness coating on rough titanium substrate in the osteogenic properties of human bone cells

Abstract: This study evaluated the effect of a bioactive ceramic coating, in the nanothickness range, onto a moderately rough surface on the osteogenic behavior of human bone cells. The cells were harvested from the mandibular mental region and were cultured over Ti-6Al-4V disks of different surfaces: as-machined (M), alumina-blasted/acid etched (AB/AE), and alumina-blasted/acid-etched + 300-500 nm thickness amorphous Ca- and P-based coating obtained by ion beam-assisted deposition (Nano). The culture was then evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Though the effects of nano-and microrough titanium topography on osteoblast behavior have been extensively described, [18][19] assays in which monocyte/macrophage behavior is examined are useful determinants for elucidating several aspects of cell interactions with implant biomaterials. 6,11,20 Mononuclear cells, especially monocytes/macrophages, were chosen for this research due to their pivotal role in wound healing, 8 producing a range of molecules which have the potential to modulate the repair process, driving the duration and intensity of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Though the effects of nano-and microrough titanium topography on osteoblast behavior have been extensively described, [18][19] assays in which monocyte/macrophage behavior is examined are useful determinants for elucidating several aspects of cell interactions with implant biomaterials. 6,11,20 Mononuclear cells, especially monocytes/macrophages, were chosen for this research due to their pivotal role in wound healing, 8 producing a range of molecules which have the potential to modulate the repair process, driving the duration and intensity of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Although exciting theories for osteoconduction of CaP nanocoatings have been described and a vast number of promising in vitro and animal studies exist, the exact mechanism behind the biological response of CaP coatings is still unclear. It has also been reported that CaP nanocoating does not favor in vitro osteogenesis [ 36 ], and a recent well-controlled in vivo study in dogs could not either confi rm that CaP nanocoatings improve early bone integration [ 37 ].…”
Section: Inorganic Coatingsmentioning
confidence: 99%
“…Surfaces of the orthopedic bioimplants serve as the site of interaction for surrounding living tissue. Hence, it is imperative to enhance the biological performance of these bioimplants using bioactive nanomaterials [27][28][29][30][31][32]. Surface engineering using nanomaterials and other suitable coating technologies aims to design and develop the bioimplants with improved osseointegration for orthopedic applications [28,33,34].…”
Section: Introductionmentioning
confidence: 99%